The Effect of Supply Chain Strategy and Marketing Mixes on Purchase Decisions Sharia Productin Palembang Region - Sri Rahayu; Cica Satria (International Journal of Supply Chain Management, 2019)
The formulation of the problem in this study is is there any influence of the marketing mix (product, price, distribution and promotion) on the purchase decision of Palembang sharia products. The purpose of this study was to determine the effect of the marketing mix (product, price, distribution and promotion) and supply chain strategy on purchasing decisions on sharia products in the Palembang region. This research includes associative research that connects two or more variables, namely the independent variable (Product, Price, Distribution, Promotion) and the dependent variable (Purchasing Decision).The population in this study were consumers in the Palembang region. The sampling technique is the accidental sampling technique. The number of samples taken 100 respondents. The data needed is primary data while the method of data collection uses the questionnaire method. The analysis technique used is multiple linear regression, f test and t test. The results of the F-test study together / simultaneous indicate that there is an influence of the marketing mix (product, price, distribution and promotion) on purchasing decisions on sharia products in Palembang. The results of the t test one by one / partial shows that there is an influence of the marketing mix (product, price, distribution and promotion) on the purchase decision of sharia products in Palembang.